2010
DOI: 10.4103/0256-4947.67075
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and obstetric outcomes in Saudi Arabia: a prospective cohort study

Abstract: BACKGROUND AND OBJECTIVES:We examined the effect of body mass index in early pregnancy on pregnancy outcome since no study in Saudi Arabia has addressed this question.METHODS:This prospective cohort study involved women registered for antenatal care during the first month of pregnancy at primary health care centers in Al-Hassa, Saudi Arabia. Data was collected from records and by direct interview.RESULTS:The study included 787 women. Compared to normal weight women (n=307), overweight (n=187) and obese (n=226)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
46
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 25 publications
15
46
4
1
Order By: Relevance
“…From the Pearson correlation value (Table 4 and Figure 3) then shows a linear correlation found for all trimester levels between body mass index and other indices. This is in agreement to finding from a recent study in Saudi Arabia according to El-Gilary and Hammad [15]. However; WHtR show a significant positive rank correlation; with BMI as an independent variable in first trimester alone with value against a (r=0.165) in WHtR.…”
Section: Discussionsupporting
confidence: 92%
“…From the Pearson correlation value (Table 4 and Figure 3) then shows a linear correlation found for all trimester levels between body mass index and other indices. This is in agreement to finding from a recent study in Saudi Arabia according to El-Gilary and Hammad [15]. However; WHtR show a significant positive rank correlation; with BMI as an independent variable in first trimester alone with value against a (r=0.165) in WHtR.…”
Section: Discussionsupporting
confidence: 92%
“…However, this can be excluded in our study, as food and water consumption throughout pregnancy did not differ between the EtOH and Control dams. Additionally, there were no differences in other maternal parameters known to affect offspring metabolic outcome, such as obesity (Whitaker, ; El‐Gilany & Hammad, ; Janjua et al . ), gestational weight gain (Margerison Zilko et al .…”
Section: Discussionmentioning
confidence: 99%
“…13 A prospective study in Saudi Arabia also reported an increased risk of GDM and pre-eclampsia with obesity. 14 In a large populationbased 15-year cohort study, obese women showed an increased risk of pregnancy-induced hypertension, with an adjusted OR of 2.38 and 3.00 for moderate and severe obesity, respectively. 15 McDonald et al conducted a systematic review and meta-analysis of 84 studies (including 64 cohort and 20 case-control studies) on 1,095,834 women; the authors concluded that obese women had a higher risk of preterm delivery (OR: 1.24; 95% CI: 1.13-1.27).…”
Section: Discussionmentioning
confidence: 99%